Status of Agroforestry contract farming for the paper industry in Jayamkondan block of Ariyalur district, Tamil Nadu - Surabi, G. (Indian Forester, 2022)
Agroforestry contract farming is on the increase worldwide. Both the state and private industries have been looking to contract with small farmers to grow tree crops in their lands to meet the requirements of increasing demand and the problem of overfelling of forests for wood resources. Various reasons have been cited about small farmers’ preferences over large farmers in agroforestry contracts by the companies and multiple factors motivate the participation of small farmers in these contracts. This article reviews the literature on agroforestry contract farming. It uses empirical evidence from Tamil Nadu, India, to identify the various factors influencing small farmers’ participation in these contract farming ventures. It also discusses the state’s role in promoting and enforcing these contracts. The study’s main findings are that per cent of dry land area in the total land is the most significant factor influencing small farmers’ participation in agroforestry contract farming.